Recycling of LiNi1/3Co1/3Mn1/3O2 cathode materials from spent lithium-ion batteries using mechanochemical activation and solid-state sintering. (1st February 2019) - Meng, Xiangqi; Hao, Jie; Cao, Hongbin; Lin, Xiao; Ning, Pengge; Zheng, Xiaohong; Chang, Junjun; Zhang, Xihua; Wang, Bao; Sun, Zhi
Graphical abstract: Highlights: A process to directly regenerate spent LiNi1/3 Co1/3 Mn1/3 O2 is demonstrated. This process incorporates mechanochemical activation and solid-state sintering. This method can restore the layered structure and improve lithium ion diffusion. Secondary pollution will not be introduced in this regeneration process. The economic viability of this method is better than a metallurgical process. Abstract: The production of lithium-ion battery is around 9100 million sets in 2016 and is believed to further increase consecutively. This fact triggers the generation of spent cathode materials which contain metals of both valuable and hazardous. Their recycling corresponding to life cycle sustainability of lithium-ion battery has attracted significant attention. However, most technologies for recycling waste lithium-ion batteries are dependent on metallurgical based processes where secondary pollution is inevitable. This research demonstrates a process to directly regenerate LiNi1−x−y Cox Mny O2 cathode material by incorporating methods of mechanochemical activation and solid-state sintering, which can restore the layered structure and improve the lithium ion diffusion without introducing extra impurities. By understanding the effects of sintering temperature, the optimal conditions for direct regeneration of cathode materials with obvious improvement on electrochemical performance can be obtained. As a result, this research proves the possibility of direct regeneration of nickel-containing waste cathode materials with minimized chemical consumption.